Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

Impact of co-exposure to Chaetoceros spp. and Tenacibaculum maritimum on Atlantic salmon (Salmo salar) gills - E. Fajei; S.K. Whyte; M. Soto-Davila; K. Eslamloo; L. Groves; K. Storey; R. Ghanei-Motlagh; D.B. Groman; S.L. Purcell; M.D. Fast (Aquaculture, 2026)

Alpha-ketoglutarate supplementation differently modifies hematological parameters and oxidative stress in mice fed a standard diet and high-fat high-fructose diet - Myroslava V. Vatashchuk; Viktoriia V. Hurza; Oleksandra B. Abrat; Maria P. Lylyk; Khrystyna Matvieieva; Dmytro V. Gospodaryov; Oleh I. Demianchuk; Kenneth B. Storey; Maria M. Bayliak; Volodymyr I. Lushchak (Journal of Physiology and Biochemistry, 2025)

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Reactivation of abandoned oilfields for cleaner energy generation: Two-dimensional modelling of lateral stratigraphic variations - Benjamin M. Storey; Richard H. Worden; David D. McNamara; John Wheeler; Julian Parker; Andre Kristen (Marine and Petroleum Geology, 2025)

Detailed hydrocarbon speciation and particulate matter emissions during cold-start from turbocharged and naturally aspirated trucks - Melanie Moses-DeBusk; John M.E. Storey; Samuel A. Lewis Sr.; R. Maggie Connatser; Shannon M. Mahurin; Shean Huff; Cyril V. Thompson; Yensil Park (Fuel, 2023)

Sedimentary provenance in continental rifts: U–Pb detrital zircon, Nd and Sr isotopes and lithogeochemistry of the Eocene alluvial sandstones of the Resende Basin, SE–Brazil - Manuela de Oliveira Carvalho; Catherine M. Mottram; Claudio de Morisson Valeriano; Renato Rodriguez Cabral Ramos; Randall Parrish; Joseph Dunlop; Natália Cota; Gabriel Paravidini; Carla Cristine Aguiar Neto; Monica Heilbron; Craig Storey (Sedimentary Geology, 2023)

Mineral-whole rock isotope fidelity? A comparative study of Hf-Nd-O from high Ba-Sr granitoids - E. Bruand; C. Storey; M. Fowler; B. Dhuime; R. Doucelance (Chemical Geology, 2023)

The upper Pleistocene (1.8–0.7 Ma) explosive eruptive history of Las Cañadas, ocean-island volcano, Tenerife - P. Dávila-Harris; M.J. Branney; M. Storey; R.N. Taylor; J.T. Sliwinski (Journal of Volcanology and Geothermal Research, 2023)

Hypoxia inducible factor-1α responds to freezing, anoxia and dehydration stresses in a freeze-tolerant frog - Janet M. Storey; Zhenhong Li; Kenneth B. Storey (Cryobiology, 2023)

Designing experimental conditions to use the Lotka–Volterra model to infer tumor cell line interaction types - Heyrim Cho; Allison L. Lewis; Kathleen M. Storey; Helen M. Byrne (Journal of Theoretical Biology, 2023)

High stability of blood parameters during mouse lifespan: sex-specific effects of every-other-day fasting - Maria M. Bayliak; Oksana M. Sorochynska; Oksana V. Kuzniak; Ivanna Z. Drohomyretska; Andriy Ya. Klonovskyi; Anastasia O. Hrushchenko; Myroslava V. Vatashchuk; Nadia M. Mosiichuk; Kenneth B. Storey; Olga Garaschuk; Volodymyr I. Lushchak (Biogerontology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A landscape‐scale framework to identify refugia from multiple stressors - Isabel M. Rojas; Megan K. Jennings; Erin Conlisk; Alexandra D. Syphard; Jack Mikesell; Alicia M. Kinoshita; Krista West; Doug Stow; Emanuel Storey; Mark E. De Guzman; Diane Foote; Alexandria Warneke; et al. (Conservation Biology, 2022)
From a conservation perspective, quantifying potential refugial capacity has been predominantly focused on climate refugia, which is critical for maintaining the persistence of species and ecosystems. However, protection from other stressors, such as human‐induced changes in fire and hydrology, that cause habitat loss, degradation, and fragmentation is also necessary to ensure that conservation efforts focused on climate are not undermined by other threats. Thus, conceptual and methodological advances for quantifying potential refugia from multiple anthropogenic stressors are important to support conservation efforts. We devised a new conceptual approach, the domains of refugia, for assessing refugial capacity that identifies areas where exposure to multiple stressors is low. In our framework, patterns of environmental variability (e.g., increased frequency of warm summers), thresholds of resilience, and extent and intensity of stressors are used to identify areas of potential refugia from a suite of ongoing anthropogenic stressors (e.g., changes in fire regime). To demonstrate its utility, we applied the framework to a Southern California landscape. Sites with high refugial capacity (super‐refugia sites) had on average 30% fewer extremely warm summers, 20% fewer fire events, 10% less exposure to altered river channels and riparian areas, and 50% fewer recreational trails than the surrounding landscape. Our results suggest that super‐refugia sites (∼8200 km 2 ) for some natural communities are underrepresented in the existing protected area network, a finding that can inform efforts to expand protected areas. Our case study highlights how considering exposure to multiple stressors can inform planning and practice to conserve biodiversity in a changing world.

Middle aged turn point in parameters of oxidative stress and glucose catabolism in mouse cerebellum during lifespan: minor effects of every-other-day fasting - Maria M. Bayliak; Nadia M. Mosiichuk; Oksana M. Sorochynska; Oksana V. Kuzniak; Lesia O. Sishchuk; Anastasiia O. Hrushchenko; Alina O. Semchuk; Taras V. Pryimak; Yulia V. Vasylyk; Dmytro V. Gospodaryov; Kenneth B. Storey; Olga Garaschuk; et al. (Biogerontology, 2021)

Every-other-day fasting reduces glycolytic capability in the skeletal muscle of young mice - Oksana M. Sorochynska; Oksana V. Kuzniak; Maria M. Bayliak; Yulia V. Vasylyk; Kenneth B. Storey; Volodymyr I. Lushchak (Biologia, 2021)

Extended liquid chromatography high resolution mass spectrometry screening method for veterinary drug, pesticide and human pharmaceutical residues in aquaculture fish - Sherri B. Turnipseed; Joseph M. Storey; I-Lin Wu; Wendy C. Andersen; Mark R. Madson (Food Additives & Contaminants: Part A, 2019)

Impacts of Air-Fuel Stratification in ACI Combustion on Particulate Matter and Gaseous Emissions - Melanie Moses-DeBusk; Scott J. Curran; Samuel A. Lewis; R. Maggie Connatser; John M. E. Storey (Emission Control Science and Technology, 2019)

Metformin as a geroprotector: experimental and clinical evidence - Veronika Piskovatska; Nadiya Stefanyshyn; Kenneth B. Storey; Alexander M. Vaiserman; Oleh Lushchak (Biogerontology, 2019)

Acute exposure to copper induces variable intensity of oxidative stress in goldfish tissues - Viktor V. Husak; Nadia M. Mosiichuk; Olga I. Kubrak; Tetiana M. Matviishyn; Janet M. Storey; Kenneth B. Storey; Volodymyr I. Lushchak (Fish Physiology and Biochemistry, 2018)

Dietary l-arginine accelerates pupation and promotes high protein levels but induces oxidative stress and reduces fecundity and life span in Drosophila melanogaster - Maria M. Bayliak; Maria P. Lylyk; Oksana V. Maniukh; Janet M. Storey; Kenneth B. Storey; Volodymyr I. Lushchak (Journal of Comparative Physiology B, 2018)

Biomimetic Dissolution: A Tool to Predict Amorphous Solid Dispersion Performance - Michael M. Puppolo; Justin R. Hughey; Traciann Dillon; David Storey; Susan Jansen-Varnum (AAPS PharmSciTech, 2017)

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Pollutant emissions and environmental assessment of ethyl 3-ethoxybutyrate, a potential renewable fuel - John M. E. Storey; Michael P. Bunce; Edwina M. Clarke; Jennifer W. Edmonds; Robert H. Findlay; Stephen M. C. Ritchie; Laurent Eyers; Zackery A. McMurry; James C. Smoot (Environmental Science and Pollution Research, 2016)

Turn down genes for WAT? Activation of anti-apoptosis pathways protects white adipose tissue in metabolically depressed thirteen-lined ground squirrels - Samantha M. Logan; Bryan E. Luu; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2016)

Response of the JAK-STAT pathway to mammalian hibernation in 13-lined ground squirrel striated muscle - Samantha M. Logan; Shannon N. Tessier; Joann Tye; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2016)

Analysis of lasalocid residues in grease and fat using liquid chromatography-mass spectrometry - Susan B. Clark; Joseph M. Storey; Justin R. Carr; Mark Madson (Food Additives & Contaminants: Part A, 2015)

A rapid liquid chromatography determination of free formaldehyde in cod - Joseph M. Storey; Wendy C. Andersen; Andrea Heise; Sherri B. Turnipseed; Jack Lohne; Terri Thomas; Mark Madson (Food Additives & Contaminants: Part A, 2015)

Oxidative stress as a mechanism for toxicity of 2,4-dichlorophenoxyacetic acid (2,4-D): studies with goldfish gills - Tetiana M. Atamaniuk; Olga I. Kubrak; Kenneth B. Storey; Volodymyr I. Lushchak (Ecotoxicology, 2013)

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

Phosphorylation of translation factors in response to anoxia in turtles, Trachemys scripta elegans: role of the AMP-activated protein kinase and target of rapamycin signalling pathways - Mark H. Rider; Nusrat Hussain; Stephen M. Dilworth; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2009)

AMP-deaminase from goldfish white muscle: regulatory properties and redistribution under exposure to high environmental oxygen level - Volodymyr I. Lushchak; Viktor V. Husak; Janet M. Storey; Kenneth B. Storey (Fish Physiology and Biochemistry, 2009)

Genetic structure of Melanotaenia australis at local and regional scales in the east Kimberley, Western Australia - R. D. Phillips; A. W. Storey; M. S. Johnson (Journal of Fish Biology, 2009)
The Kimberley region of Western Australia possesses a poorly studied freshwater fish fauna with high endemism in an aquatic landscape subject to monsoonal floods and dry season isolation. In the first population genetic study of freshwater fish in this region, the authors tested the effects of geographic barriers on genetic structure at multiple spatial scales in east Kimberley populations of the western rainbowfish, Melanotaenia australis , the most widespread and abundant species in the region. Based on allozyme comparisons, hierarchical analysis of F ST revealed increasing genetic subdivision with spatial scale. Minimal genetic structure within creeklines demonstrated that wet season dispersal, rather than dry season isolation, determines genetic structure at small scales. At the scale of sub‐catchments, a pattern of isolation by distance along creeklines was evident. Genetic subdivision between adjacent river systems was greater between rivers separated by a plateau than by lowlands. This implies greater connectivity of populations in lowland areas and may explain the greater similarity of the east Kimberly freshwater fish fauna with lowlands to the east than with the more rugged regions to the west. Similarly, greater connectivity between lowland populations may account for the on‐average larger distribution of lowland Melanotaeniids.

Composition and temporal changes in macroinvertebrate communities of intermittent streams in Hawke's Bay, New Zealand - Richard G. Storey; John M. Quinn (New Zealand Journal of Marine and Freshwater Research, 2008)
Macroinvertebrate communities in three stony‐bottomed intermittent headwater streams in central Hawke's Bay, New Zealand, were sampled once per month (on average) for 11 months from autumn 2005 to summer 2006, and compared with communities in three perennial streams and three intermittent streams with perennial headwaters. Among the intermittent headwater sites, 95 taxa were found, with Oligochaeta, Copepoda, Chironomidae, and Ostracoda occurring in greatest abundance. Eight mayfly, 6 stonefly and 16 caddisfly species were found. Macroinvertebrate abundance at intermittent headwater sites was equal to nearby perennial sites, but taxon richness per sample was lower. Community composition changed progressively during the autumn‐to‐spring flow period (March‐November 2005) at one intermittent headwater site, but at the other two sites a directional change was not evident, probably because stream flow stopped briefly several times during the flow period. Most of the taxa collected in riffles during the flow period were also in disconnected pools after flow stopped in summer (January 2006), but some taxa were absent and the disconnected pools contained several additional species. The disconnected pools in January had higher macroinvertebrate density and richness than connected pools during the flow period. At intermittent sites with perennial headwaters, taxon richness and EFT (Ephemeroptera, Plecoptera, and Trichoptera) richness were intermediate between intermittent headwater sites and perennial streams. Two weeks after flow began, the intermittent sites with perennial headwaters showed much higher EPT abundance and richness than the intermittent headwater sites, but after 8 weeks the proportional difference was less.

Freezing and anoxia tolerance of slugs: a metabolic perspective - Kenneth B. Storey; Janet M. Storey; Thomas A. Churchill (Journal of Comparative Physiology B, 2007)

The Canon of Potato Science - P. C. Struik; W. J. M. Lommen; A. J. Haverkort; R. M. J. Storey (Potato Research, 2007)

The Canon of Potato Science: 44. Damage and Bruising - R. M. J. Storey (Potato Research, 2007)

Influence of type of cancer and hematopoietic stem cell transplantation on clinical presentation of Pneumocystis jiroveci pneumonia in cancer patients - H. A. Torres; R. F. Chemaly; R. Storey; E. A. Aguilera; G. M. Nogueras; A. Safdar; K. V. I. Rolston; I. I. Raad; D. P. Kontoyiannis (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Liver fatty acid binding protein expression enhances branched-chain fatty acid metabolism - Barbara P. Atshaves; Stephen M. Storey; Huan Huang; Friedhelm Schroeder (Molecular and Cellular Biochemistry, 2004)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Estrogen receptor-α and -β immunoreactivity and mRNA in neurons of sensory and autonomic ganglia and spinal cord - R.E. Papka; M. Storey-Workley; P.J. Shughrue; I. Merchenthaler; J.J. Collins; S. Usip; P.T.K. Saunders; M. Shupnik (Cell and Tissue Research, 2001)

Biological, chemical and physical characteristics of downwelling and upwelling zones in the hyporheic zone of a north-temperate stream - Rob J. M. Franken; Richard G. Storey; D. Dudley Williams (Hydrobiologia, 2001)

Effects of Seed-Borne Microdochium Nivale on Establishment and Population Density at Harvest of Winter-Sown Oats - J. Humphreys; B. M. Cooke; T. Storey (Cereal Research Communications, 1997)